A multi-agent system for computational problem solving - a review - Rajabi, Maryam; Mohd Aris, Teh Noranis (Institute of Research Engineers and Doctors, 2014)
Computational problem solving is taken into account as the first step before source code development. However, novice students face difficulties in understanding problem statements and transforming them to computational problem solving techniques. This requires the understanding of fundamental programming concepts. It is very important to cater this problem from the beginning before writing the source codes. This article reviews current studies on the designed environments for problem solving and the possibility to propose a new architecture for computational problem solving utilizing multi-agent technology.